Parity sheaves, moment graphs and the p-smooth locus of Schubert varieties - Fiebig, Peter; Williamson, Geordie (Annales de l'Institut Fourier, 2014)
We show that the Braden-MacPherson algorithm computes the stalks of parity sheaves. As a consequence we deduce that the Braden-MacPherson algorithm may be used to calculate the characters of tilting modules for algebraic groups and show that the p-smooth locus of a (Kac-Moody) Schubert variety coincides with the rationally smooth locus, if the underlying Bruhat graph satisfies a GKM-condition.
Keywords: Constructible sheaves; Equivariant cohomology; Modular representation theory; Moment graphs; p-smooth locus; Schubert varieties; Tilting modules